조기정신증 대상자를 위한 지역사회 기반 사례관리 경험: Social Treatment for Early Psychosis 프로그램을 중심으로 - 신소연; Shin Soyoun; 최희승; Choi Heeseung (정신간호학회지, 2021)
Purpose: The purpose of this study was to explore the experience of case management for early psychosis and identify factors influencing care management. Methods: We conducted in-depth interviews with 10 mental health professionals who implemented the Social Treatment for Early Psychosis (STEP) program. The collected data were analyzed using qualitative content analysis. Results: The findings consisted of 4 categories and 15 subcategories. Case management should develop expertise considering the desires of young adults, and grew as experts by promoting family cooperation and coping with mental crises. Administrator's support and peer support programs had a positive impact, while the absence of collaborative systems with psychiatric institution were identified as limitations in the operating system of the basic center. Consulting and monitoring of the metropolitan center provided a foundation for case management at the basic center, while the government's support policy is needed to improve of working environment and set up the youth-friendly early intervention system. Conclusion: The results suggest that case management for early psychosis requires multilateral and cooperative efforts by strengthening the capabilities of case managers, establishing an integrated case management network of basic and metropolitan centers, and expanding the government's human and physical infrastructure.